Search for new physics in the monophoton final state in proton-proton collisions at root s=13 TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; Fruehwirth,R; et al. (Journal of High Energy Physics, 2017)
A search is conducted for new physics in a final state containing a photonand missing transverse momentum in proton-proton collisions at √s = 13 TeV. The datacollected by the CMS experiment at the CERN LHC correspond to an integrated luminosityof 12.9 fb−1. No deviations are observed relative to the predictions of the standard model.The results are interpreted as exclusion limits on the dark matter production cross sectionsand parameters in models containing extra spatial dimensions. Improved limits are set withrespect to previous searches using the monophoton final state. In particular, the limits onthe extra dimension model parameters are the most stringent to date in this channel.